Is The Pls Financing Scheme Better Than Non-Pls for Profitability Islamic Bank? Indonesian Case - Kurnia, Pipin; Darlis, Edfan; Agusti, Restu; Supriono, Supriono; Wiguna, Meilda; Masrizal, Masrizal (Integrated Journal of Business and Economics (IJBE), 2025)
The expanding presence and assets of Islamic banking within the national banking industry necessitate an analysis of Islamic banking's performance. This study examines the effects of various PLS and non-PLS financing schemes on the profitability of Islamic banks in Indonesia using the ARDL method and monthly data from 2009 to 2021. Results indicate that using the PLS financing scheme considerably positively impacts Islamic banking's profitability. Meanwhile, the non-PLS financing scheme has a significant negative impact on Islamic bank profitability. Intriguingly, the contribution of PLS financing to Islamic bank profitability is superior to that of non-PLS financing. In light of this crucial contribution, regulators need incentives and regulations to maximize PLS-based financing. Therefore, Islamic banks must implement concrete measures and initiatives to increase Islamic financing under PLS arrangements if Islamic finance is to grow significantly.